2023
DOI: 10.1002/adma.202206956
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐Modulated Untwist Deformations and Multispectral Optical Effects from Ion Intercalation into Chiral Ceramic Nanoparticles

Abstract: Reconfiguration of chiral ceramic nanostructures after ion intercalation should favor specific nanoscale twists leading to strong chiroptical effects.  In this work, V2O3 nanoparticles are shown to have “built‐in” chiral distortions caused by binding of tartaric acid enantiomers to the nanoparticle surface. As evidenced by spectroscopy/microscopy techniques and calculations of nanoscale chirality measures, the intercalation of Zn2+ ions into the V2O3 lattice results in particle expansion, untwist deformations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Transmission electron microscopy (TEM) images showed that the chiral d/l -V 2 O 3 /VN NPs had sizes of about 2.12 ± 0.17 nm. High-resolution TEM images showed that the d/l -V 2 O 3 /VN NPs had a lattice spacing of about 0.21 nm, which is consistent with the (610) planes of monoclinic V 2 O 3 (Figures B and S1). The dynamic light scattering results for l -V 2 O 3 /VN confirmed the size of the NPs (Figure S2).…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…Transmission electron microscopy (TEM) images showed that the chiral d/l -V 2 O 3 /VN NPs had sizes of about 2.12 ± 0.17 nm. High-resolution TEM images showed that the d/l -V 2 O 3 /VN NPs had a lattice spacing of about 0.21 nm, which is consistent with the (610) planes of monoclinic V 2 O 3 (Figures B and S1). The dynamic light scattering results for l -V 2 O 3 /VN confirmed the size of the NPs (Figure S2).…”
Section: Resultssupporting
confidence: 59%
“…Fourier transform infrared (FTIR) spectroscopy (Figure S5) showed that the peaks associated with the −OH, C�O, and C−O vibrations in Tar were significantly shifted, indicating that Tar was bound to the V 2 O 3 /VN NPs. 54 The ζ potential values of the L-V 2 O 3 /VN NPs and D-V 2 O 3 /VN NPs in water were −29.1 and −31.2 mV, respectively (Figure S6). The CD spectrum of chiral V 2 O 3 /VN showed four strong peaks at 400, 523, 634, and 906 nm (Figure 1C).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface chiral modification of nanomaterials provides an alternative approach to tune the band gap. ,, Previous research has shown that chiral nanomaterials often exhibit unique light–electron interaction behavior, resulting in a CD intensity of 0 mdeg at the band gap edge of the material and strong CD signals at weak valence electron transitions due to the Cotton effect, the multiple exciton coupling effect, the long-range hyperconjugation effect, , van der Waals interactions, and the scattering effect . Consequently, this brings about significant changes in the photocatalytic reaction of TiO 2 and highlights the importance of preparing chiral TiO 2 with a CD signal in the NIR; using this strategy, it is possible to use circularly polarized light (CPL) to excite a catalyst, , thus providing another way for advancements in this field.…”
Section: Introductionmentioning
confidence: 99%